2017
DOI: 10.1016/j.ypmed.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

“Monkey see, monkey do”: Peers' behaviors predict preschoolers' physical activity and dietary intake in childcare centers

Abstract: Preschoolers observe and imitate the behaviors of those who are similar to them. Therefore, peers may be important role models for preschoolers' dietary intake and physical activity in childcare centers. This study examined whether peers' behaviors predict change in preschoolers' dietary intake and physical activity in childcare centers over 9 months.A total of 238 preschoolers (3 to 5 years old) from 23 childcare centers in two Canadian provinces provided data at the beginning (October 2013 and 2014) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(32 reference statements)
2
13
0
Order By: Relevance
“…Sibling and peer PA and sedentary behaviors appear to be important influences on preschool‐aged children's PA and sedentary behaviors. Preschoolers observe and imitate the behaviors of those who are similar to them (Ward et al., ). Therefore, siblings and peers may be role models for preschoolers' PA. A study conducted in childcare centers in Canada found that peers influenced preschoolers’ PA over time (Ward et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sibling and peer PA and sedentary behaviors appear to be important influences on preschool‐aged children's PA and sedentary behaviors. Preschoolers observe and imitate the behaviors of those who are similar to them (Ward et al., ). Therefore, siblings and peers may be role models for preschoolers' PA. A study conducted in childcare centers in Canada found that peers influenced preschoolers’ PA over time (Ward et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Preschoolers observe and imitate the behaviors of those who are similar to them (Ward et al, 2017). Therefore, siblings and peers may be role models for preschoolers' PA. A study conducted in childcare centers in Canada found that peers influenced preschoolers' PA over time (Ward et al, 2017).…”
Section: Siblings and Peer Influencesmentioning
confidence: 99%
“…Time spent in physical activity (PA), moderate-tovigorous PA (MVPA), light intensity PA (LPA) and sedentary time were measured based on predetermined validated thresholds for preschoolers [17]. Counts of less than 25 per 15 s represented sedentary time (which included nap time) [18], counts between 25 and 714 per 15 s represented LPA [17,18] while counts of 715 and above defined MVPA [19]. Non-wear time was defined as any period of 60 consecutive minutes where no counts were measured.…”
Section: Physical Activitymentioning
confidence: 99%
“…Non-wear time was defined as any period of 60 consecutive minutes where no counts were measured. To provide the most reliable data while maximizing sample size, it was determined that children had to have worn the accelerometer for a minimum of 2 h on at least 4 days to be included in the analyses [19]. To control for within and between participant wear time variations, accelerometer data were standardized to an 8-h period, [20] which represents the typical number of hours children in our study attended the ECC.…”
Section: Physical Activitymentioning
confidence: 99%
“…After weaning, mothers (and in general parents/caregivers) are able to exert an important influence on children's vegetable preferences through the food choices provided, as well as the feeding practices, and the modeling effect that they exert on their own children (Benton, 2004;Kral & Faith, 2009;Nicklas et al, 2001). Other important influencers of children's eating habits are their siblings and peers (Lau, Quadrel, & Hartman, 1990;Pliner & Pelchat, 1986;Ward et al, 2017). Studies oriented to understanding the influence of siblings on children's eating habits have observed that older siblings are able to encourage children to eat during mealtimes, thus imitating a maternal behavior (Mosli et al, 2015).…”
mentioning
confidence: 99%